Delphi Consensus on the Management of Spanish Patients with Post-Stroke Hemiplegic Shoulder Pain Treated with Botulinum Toxin A: Result Study - Carlos Cordero-García; Irene de Torres; Jacobo Formigo-Couceiro; Lluis Guirao; Mª Dolores Romero-Torres; Sergio Otero-Villaverde; Alberto Herrera; Cristina Santa; Antonio Mena-Rodriguez (Toxins)
The study aimed to identify expert opinions and obtain recommendations on the management of post-stroke hemiplegic shoulder pain (HSP) and treatment with botulinum toxin A (BoNT-A). A multicenter Delphi study was conducted using an online survey designed by a committee of experts with at least 10 years of experience in post-stroke HSP management with BoNT-A in Spain. Forty-seven panelists (specialists with at least 5 years of experience in post-stroke HSP management with BoNT-A) rated their level of agreement in two rounds based on acceptance by ≥66.7% of them. In round 1, 245 statements on three dimensions were evaluated (diagnosis, treatment, and follow-up of the HSP patients treated with BoNT-A). A total of 159 statements (70.9%) were finally accepted after round 2. Experts recommended BoNT-A as soon as spasticity affects daily activities. They considered ultrasound as the preferred guided technique. Experts recommended regular assessments using validated scales and patient-reported outcomes to evaluate treatment goals and safety. In case of lack of response, experts suggested increasing the dose or number of treated muscles or considering alternative treatments. These consensus-based recommendations offer clinicians an approach to the management of post-stroke HSP with BoNT-A, supporting informed decision making.